ΜXRF Application for Uranium Exploration (Case Study: Mamuju Deposit, Indonesia). Issue 1 (September 2021) - Savira, D; Gunawan, M A; Draniswari, W A; Sukadana, I G; Sihombing, F
Abstract: Micro X-ray fluorescence (µXRF) is an advanced analysis technique from conventional XRF (X-Ray Fluorescence) that allows analysis of smaller areas even inclusions with irregular shapes and non-homogeneous elements. This method has a spatial resolution up to 10 µm depends on the energy by X-rays so that the excitation beam at the smallest point of the sample surface can be detected. This study explains the application of µXRF to determine the type of deposit and the formation of uranium contained in Takandeang Village, Tapalang District, Mamuju Regency, West Sulawesi. The study began with surface geological and radiometry mapping, continued with geological drilling. Collected samples then undergo petrology, petrographic, and geochemical analysis. Three collected samples from drilling sample were analysed using the µXRF. From the analyses we found that the highest uranium anomaly is found in leucitite autobreccias. The anomaly that occurred in the study area was in the form of reconcentration of uranium elements in autobreccia rocks caused by hydrothermal activity which was also supported by magma type and structural control in the study area. In this study case we found that µXRF is usefull for uranium exploration.